Bibliometric Analysis of Electrical and Electronic Equipment Production and Consumption in the Context of the Circular Economy - Ion Popa; Claudiu Cicea; Simona Catalina Stefan; Corina Marinescu; Daniel Botez (Amfiteatru Economic, 2023)
The paper aims to highlight the most relevant elements that appear at the intersection of two concepts: the circular economy and electrical and electronic equipment (EEE), as they are reflected in the mainstream of scientific publications to date. This approach is possible through the use of a bibliometric study, following which current trends and new possible perspectives and research directions could be identified to contribute to the promotion of circularity in the production and consumption of EEE. The bibliometric study also involves the temporal and geographical analysis of scientific production, the semantic analysis of keywords with their graphical representation, and the relationship among them, based on the use of specialised software (VOSViewer and Citespace). The main results refer to the existence of four clusters, grouped according to keywords with a frequency of occurrence greater than 10, which refer to EEE waste management, circular economy, material recycling, and environmental management. Regarding the intensity of keyword use, the top three places are China, product, and urban mining. In the end, the conclusions of the study are highlighted, including the grouping of keywords into thematic clusters, the identification of three periods that have been able to stand out so far in scientific research in the domain. As for the limits of the research, they take into account the database that was subjected to the analysis (in the present paper, Web of Science), the software used, the writing language of the scientific production, and the analysis interval. The article concludes with future research directions.
Keywords: Q53; 330; Circular economy (CE); consumption of electrical and electronic equipment; waste of electrical and electronic equipment (WEEE); electrical and electronic equipment (EEE); production of electrical and electronic equipment; bibliometric analysis.